State of art review on PP‑band retrofitting for masonry structures - Sathiparan, N. (Springer, 2020)
Experience from earthquakes has shown that the collapse of unreinforced masonry structures causes a larger number of loss of life during these events in developing countries. Therefore, there is an urgent need to improve their seismic performance to reduce future fatalities and to protect the existing housing stock. To efectively promote seismic retroftting, inexpensive and simple technical solutions are required. Because in many regions self-construction is predominant, it is expected that any retroftting initiative will also be taken by the house resident. Consequently, it is also important that the retroftting procedure does not require highly skilled labor. Polypropylene band (PP-band) retroftting method satisfes these two key requirements. PP-bands are commonly used for packing, which is inexpensive, worldwide available and durable. This paper focuses on reviewing the PP-band seismic retroftting considering tests conducted to evaluate the efciency of the retroftting method, factors afecting the retroftting, promotion technique, limitation and feature research focus of the PP-band retroftting method.
Keywords: PP-band; Masonry; Earthquake; Retroftting; Residual strength